An in situ photoelectroreduction approach to fabricate Bi/BiOCl heterostructure photocathodes: understanding the role of Bi metal for solar water splitting. Issue 10 (15th February 2017) - Fan, Weiqiang; Li, Chunfa; Bai, Hongye; Zhao, Yanyan; Luo, Bifu; Li, Yongjun; Ge, Yilin; Shi, Weidong; Li, Hongping
Abstract : This paper presents for the first time a novel method of in situ depositing plasmonic Bi nanoparticles on BiOCl nanosheets (Bi/BiOCl) for PEC water splitting. Abstract : This paper presents for the first time a novel method of depositing plasmonic Bi nanoparticles on BiOCl nanosheets (Bi/BiOCl) via insitu photoelectroreduction, and Bi/BiOCl as the photocathode enabled solar water splitting in a TiO2 –Bi/BiOCl photoelectrochemical (PEC) system. It is one of the challenges to understand the relationship between the PEC performance and the composite ratio of Bi/BiOCl, and the density functional theory calculation results show that charges obviously transfer from the Bi cluster to the BiOCl (001) surface. The structure of Bi/BiOCl photocathode has been successfully optimized, according to the current–potential curves and charge injection efficiency. The highly enhanced PEC activity could be attributed to the dual roles of Bi nanoparticles in enhancing the charge transfer and surface plasmon resonance (SPR) effect. More importantly, the optimal Bi/BiOCl photocathode achieved a solar hydrogen evolution rate of 2.4 µmol h −1 under full spectrum illumination (100 mW cm −2 ).